Donor after circulatory death in pancreas transplantation: a scoping review of the literature - Chassot, Mathieu; Scheen, Marc; Wassmer, Charles-Henri; Compagnon, Philippe; Peloso, Andrea; Haidar, Fadi (Frontiers in Transplantation, 2025)
The growing disparity between the demand for pancreas transplants and the availability of suitable organs underscores the urgent need for innovative donor strategies, including the utilization of donors after circulatory death (DCD). This scoping review presents a comprehensive comparative analysis of transplantation outcomes between DCD and donors after brain death (DBD), focusing on pancreatic graft survival, postoperative complications, and functional metrics such as graft performance and HbA1c levels. Although DCD grafts were suspected to be associated with higher rates of early complications, including delayed graft function and thrombosis, altogether resulting from potentially more ischemia-reperfusion injuries, their long-term outcomes are comparable to those of DBD grafts. This equivalence is likely driven by careful donor selection, a meticulous pancreas procurement, use of normothermic regional perfusion and a short ischemic time. The findings highlight the transformative potential of DCD donors in expanding the pancreas donor pool, addressing critical organ shortages, and enhancing transplant accessibility. This review advocates for the integration of DCD donors into routine clinical practice, emphasizing the need for optimized clinical protocols and organ allocation strategies. By leveraging DCD donors more effectively, the transplant community can make significant strides in improving patient outcomes and addressing the global organ shortage crisis.